DEVELOPMENT OF A PROCESS FOR CANNING FRESH WATER FISH ROHU (LABEO ROHITA) - BALACHANDRAN, K K; VIJAYAN, P K (Fishery Technology, 2017)
Results of experiments conducted to work out a process for canning fresh water :fish rohu ( Labeo rohzta) from culture sources are presented. In order to impart a proper :firm texture to the meat cold blanching the skinless boneless meat in 15 % brine containing 0.25 % calcium chloride was found necessary. Increasing the concentration of calcium chloride beyond 0.25 % resulted in impairing the quality of meat, the texture becoming more :fibrous and the flavour being adversely effected. Other firming agents tried did not yield any beneficial effect. The meat so blanched yielded a good product when canned in ’natural style.’